2018
DOI: 10.1186/s12936-018-2177-9
|View full text |Cite
|
Sign up to set email alerts
|

Preventing malaria in the Peruvian Amazon: a qualitative study in Iquitos, Peru

Abstract: BackgroundIn Peru, despite decades of concerted control efforts, malaria remains a significant public health burden. Peru has recently exhibited a dramatic rise in malaria incidence, impeding South America’s progress towards malaria elimination. The Amazon basin, in particular the Loreto region of Peru, has been identified as a target for the implementation of intensified control strategies, aiming for elimination. No research has addressed why vector control strategies in Loreto have had limited impact in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 33 publications
6
17
0
Order By: Relevance
“…This perception may be the impact of different stakeholders working to improve sanitation and hygiene, or it may be misunderstanding of the taught on management of the environment to avoid pooling of water around the compound to prevent the breeding of mosquito vectors which further implies poor awareness creation for informed decision by the community to participate in combating malaria. This finding was in line with results from Konso [28], Jima [29], Mandura district in Benishangul-Gumz region [34], an article published in 1992 among Adangibe farming community in Ghana [38,39] and Lereto area in Peru [31] but not with findings in Gabon [30], Kersa district in eastern Ethiopia [26], and Ghana [35]. These disagreements could be due to differences in the awareness among the study population as those in Kersa district are exposed more on different researches since it has been serving as Health and demographic research site for Haromaya University.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This perception may be the impact of different stakeholders working to improve sanitation and hygiene, or it may be misunderstanding of the taught on management of the environment to avoid pooling of water around the compound to prevent the breeding of mosquito vectors which further implies poor awareness creation for informed decision by the community to participate in combating malaria. This finding was in line with results from Konso [28], Jima [29], Mandura district in Benishangul-Gumz region [34], an article published in 1992 among Adangibe farming community in Ghana [38,39] and Lereto area in Peru [31] but not with findings in Gabon [30], Kersa district in eastern Ethiopia [26], and Ghana [35]. These disagreements could be due to differences in the awareness among the study population as those in Kersa district are exposed more on different researches since it has been serving as Health and demographic research site for Haromaya University.…”
Section: Discussionsupporting
confidence: 91%
“…Less is known about the perception of parents of SAC on the cause of malaria and their experience on the control of malaria. The perception of parents on the cause of malaria are diverse and context dependent: some consider it as supernatural [30] while others associate it with poor environmental and personal hygiene, consumption of contaminated water or food, exposure to different weather condition to mention few among others [28,29,31]. However, the existing information was not sufficient to develop malaria prevention education that might help in controlling malaria in Ethiopia and other similar contexts.…”
Section: Introductionmentioning
confidence: 99%
“…In all these studies, these factors consistently resulted in intermittent LLIN use. Longer durations of exposure to mosquitoes due to a number of factors, such as heat or customs of talking at night outdoors, are similar to those in other countries [47,54]. However, entomological data from PALEVALUT has shown that the bites of the mosquitoes responsible for malaria in the 2 study sites, Brickaville and Ankazobe, are 2 to 6 times more intense outdoors than indoors.…”
Section: Sociocultural Factors In Madagascar and Elsewheresupporting
confidence: 52%
“…Some data suggest that infected An. darlingi tend to bite more outdoors and in the early evening, which reduces the effectiveness of bed nets (Moreno et al, 2015 ; Newell et al, 2018 ). The (EIR) is the current gold standard to estimate malaria transmission intensity.…”
Section: Discussionmentioning
confidence: 99%